The Association Between Genetic Variation in FOXP2 and Sensorimotor Control of Speech Production - Zhang, Siyun; Zhao, Jiangli; Guo, Zhiqiang; Jones, Jeffery A.; Liu, Peng; Liu, Hanjun (Frontiers in Neuroscience, 2018)
Significant advances have been made in understanding the role of auditory feedback in sensorimotor integration for speech production. The neurogenetic basis of this feedback-based control process, however, remains largely unknown. Mutations of FOXP2 gene in humans are associated with severe deficits in speech motor behavior. The present study examined the associations between a FOXP2 common variant, rs6980093 (A/G), and the behavioral and event-related potential (ERP) responses to -50 and -200 cents pitch perturbations during vocal production in a sample of 133 Chinese adults. Behaviorally, the GG genotype was associated with significantly smaller vocal compensations for -200 cents perturbations relative to the AA and AG genotypes. Furthermore, both the AA and AG genotypes exhibited significant positive correlations between the degree of vocal compensation for -50 and -200 cents perturbations and the variability of normal voice fundamental frequency, whereas no such correlation existed for the GG genotype. At the cortical level, significantly larger P2 responses to -200 cents perturbations were associated with the GG genotype as compared to the AA and AG genotypes due to increased left-lateralized activity in the superior, middle, and inferior frontal gyrus, precentral gyrus, anterior cingulate cortex, middle temporal gyrus, and insula. The neurobehavioral responses to -50 cents perturbations, however, did not vary as a function of genotype. These findings present the first neurobehavioral evidence for an association between FOXP2 genetic variant and auditory-motor integration for vocal pitch regulation. The differential effects of FOXP2 genotypes at rs6980093 may reflect their influences on the weighting of feedback and feedforward control of speech production.